Mast Cells, Magnesium Chloride and Seborrheic Dermatitis as an Allergic Skin Disease - Sudan, Bernard Jean Louis (International Journal of Innovative Research in Medical Science, 2024)
Seborrheic dermatitis is a dermatological syndrome which was first described in 1887 at about the time that tobacco smoking was becoming widespread in public places. Since 1978 the study of a familial seborrheic dermatitis revealed an immune reaction to the hapten nicotine of tobacco smoke. At that time, the efficacy of a sodium cromoglycate ointment showed a potential involvement of tissue mast cells. Later the use of a soap and ointment based on Dead Sea salts proved to be effective. At the same time, several laboratories detected histamine locally in patients afflicted with seborrheic dermatitis. Dead Sea and Zechstein salts contain about 30% of magnesium chloride. Recently, the use of a magnesium chloride ointment showed a significant efficacy. Future research should investigate the exact role of magnesium chloride on tissue mast cells and especially their ion channels. The stabilization of tissue mast cells appears as a new and promising research to help patients with seborrheic dermatitis and probably other dermatological syndromes as atopic dermatitis.